RESEÑA de : Cébeillac-Gervasoni, M.; Caldelli, M.L.; Zevi, F. Épigraphie Latine. Saint-Just-La-Pendue : Armand Colin-Collection U Histoire, 2006 - Andreu Pintado, Javier (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2007)
-